(untitled) (Jurnal Manajemen Bisnis, 2024)
In today’s competitive business environment, ensuring optimal employee performance is critical for organizational success. Rewards, both intrinsic and extrinsic, play a vital role in motivating employees to perform at their best. The purpose of this study is to examine the influence of intrinsic and extrinsic rewards on employee performance. The research method used is quantitative, designed to explore specific aspects of the population and sample selected for the study. The population at PT. Bumi Lancang Kuning Pusaka consists of 119 individuals. In this study, the sample was determined using purposive sampling, resulting in 46 employees from the operational division at PT. Bumi Lancang Kuning Pusaka Pekanbaru being selected as respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) software. The findings of this study reveal that both intrinsic and extrinsic rewards partially influence employee performance. Moreover, intrinsic and extrinsic rewards simultaneously have a significant impact on employee performance.